2001
DOI: 10.1111/j.1745-9125.2001.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Covariates of U.S. County Homicide Rates: Incorporating Spatial Effects*

Abstract: Spatial analysis is statistically and substantively important for macrolevel criminological inquiry. Using county-level data for the decennial years in the 1960 to 1990 time period, we reexamine the impact of conventional structural covariates on homicide rates and explicitly model spatial effects. Important findings are: (1) homicide is strongly clustered in space; (2) this clustering cannot be completely explained by common measures of the structural similarity of neighboring counties; (3) noteworthy regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
349
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(378 citation statements)
references
References 33 publications
14
349
0
10
Order By: Relevance
“…Empirical research in criminology commonly applies regression models to explain observed variations in crime rates across geographic regions with xed boundaries such as counties (Baller et al, 2001), police precincts , census tracts (Helbich and Arsanjani, 2014), or census block groups (Willits et al 2013). The theoretical background consists of sociological theories of crime including social ecology theories and place-based theories (see, e.g., Anselin et al, 2000).…”
Section: Predictorsmentioning
confidence: 99%
“…Empirical research in criminology commonly applies regression models to explain observed variations in crime rates across geographic regions with xed boundaries such as counties (Baller et al, 2001), police precincts , census tracts (Helbich and Arsanjani, 2014), or census block groups (Willits et al 2013). The theoretical background consists of sociological theories of crime including social ecology theories and place-based theories (see, e.g., Anselin et al, 2000).…”
Section: Predictorsmentioning
confidence: 99%
“…The simple descriptive analysis of homicide data showed that urban minority males killed with guns represented the subpopulation at greatest risk for victimization. The combination of exploratory spatial data analysis and spatial regression analysis found evidence in support of the conclusion that violence was diffusing at the national level (Blumstein and Rosenfeld 1998;Cork 1999;Kellerman 1996), county level (Messner et al 1999;Baller et al 2001;Messner and Anselin 2004), and local levels (Block and Block 1993;Cohen and Tita 1999;Fagan et al 1998;Kennedy and Braga 1998;Klein et al 1991;Morenoff et al 2001). …”
Section: Ecological Studies Of Crime: the Use Of Spatial Regression Mmentioning
confidence: 90%
“…Both of these concepts combine people and space in different fashions with different effects. In choosing, for unrelated reasons, to collapse population size and density into a single index (Baller, Anselin, Messner, Deane, and Hawkins 2001;Land, McCall, and Cohen 1990), scholars lose these distinct effects .…”
Section: Population Density and Population Size: The Micro-and Macro-mentioning
confidence: 99%